2017
DOI: 10.1108/jfp-04-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient violence in a Dutch forensic psychiatric hospital

Abstract: Purpose -Inpatient violence can have a major impact in terms of traumatic experiences for victims and witnesses, an unsafe treatment climate, and high-financial costs. Therefore, the purpose of this paper is to gain more insight into patterns of violent behavior, so that adequate preventive measures can be taken. Design/methodology/approach -Data on inpatient violence in a Dutch forensic psychiatric hospital between 2008 and 2014 were extracted from hospital files on 503 patients. Findings -More than half of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Two studies found higher assault rates among patients with a nonforensic commitment type than patients with a forensic commitment (Broderick et al, 2015; Linhorst & Parker Scott, 2004). Two studies, that were conducted in the same hospital as the present study, although on different samples, found that civil patients had higher rates of verbal aggression than forensic patients, but equal rates of physically violent incidents (Verstegen et al, 2017), and that female forensic patients caused the most severe violent incidents, followed by female civil patients. Male forensic patients caused the least severe incidents (Huitema et al, 2018).…”
Section: Legal Statussupporting
confidence: 45%
See 1 more Smart Citation
“…Two studies found higher assault rates among patients with a nonforensic commitment type than patients with a forensic commitment (Broderick et al, 2015; Linhorst & Parker Scott, 2004). Two studies, that were conducted in the same hospital as the present study, although on different samples, found that civil patients had higher rates of verbal aggression than forensic patients, but equal rates of physically violent incidents (Verstegen et al, 2017), and that female forensic patients caused the most severe violent incidents, followed by female civil patients. Male forensic patients caused the least severe incidents (Huitema et al, 2018).…”
Section: Legal Statussupporting
confidence: 45%
“…Data on violent incidents that occurred between January, 2014, and December, 2019, were retrieved from daily hospital reports and patients’ medical records. The daily reports, aimed to inform patients and staff on current events in the hospital, briefly describe violent behavior and have been used as a violent incident measure in other studies (Huitema et al, 2018; Verstegen et al, 2017). If the reports stated that a violent incident occurred, subsequent information about the incident was retrieved from the patient’s medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Aggression of forensic psychiatric inpatients is highly prevalent, with recent estimates between 31% and 59% of at least one violent assault during hospitalization [1,2]. Inpatient aggression threatens safety and wellbeing of both patients and staff [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…An insanity plea is rare (0.29%–1.73%) and very few of these cases end in acquittal (0.12% and 0.52%; Cirincione et al, 1995). However, NGRI acquittees are high-risk patients for aggression during treatment and have the additional challenge of serious mental illness (SMI) (Thomson, Galusha, et al, 2020; Verstegen et al, 2017). Even though early conceptualization of psychopathy stated that psychopathic individuals should have an “absence of delusions and other signs of irrational thinking” (Cleckley, 1984, pp.…”
Section: Introductionmentioning
confidence: 99%